AICCRA 2023 Partnership Survey Results Report - Poulos, Allison; Giombini, Valentina; Calì, Davide; Ramírez, Margarita M.; Schuetz, Tonya; Marchi, Julian; Bonilla Findji, Osana (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a USD 60 million three-year project, funded by the World Bank and led by CIAT, with participating partners from seven countries: Ethiopia, Kenya, Ghana, Kenya, Mali, Senegal and Zambia. This report provides an overview of two Satisfaction Surveys that were disseminated to partners to gather their feedback on three of the intermediate Project Indicators (IPI), as laid out in the Project Implementation Arrangements. These indicators capture progress on (1 - IPI 1.3) the satisfaction with the usefulness, accessibility and relevance, particularly for gender and youth responsiveness, (2 - IPI 2.4) effectiveness of partnerships, and (3 - IPI 3.3) the use or adaptation of AICCRA-funded climate-relevant knowledge products, decision-making tools and services. Both surveys were from 14 November – 4 December 2023. For the AICCRA Partnership Satisfaction Survey, the cluster leads provided the products/services to survey for their cluster, and they sent the survey to their partners totaling 380 recipient emails. There were 280 responses, which results in a 74% response rate. For the AICCRA Partnership Efficiency Survey, the survey was sent to 258 partners, and there were 142 responses resulting in a 55% response rate. Of the 142 responses, 137 were eligible for analysis. Survey results indicate all third-year targets were achieved. Satisfaction with the products and services of the project (IPI 1.3) attained an average of 83%, 8% over the target of 75%. Effectiveness of partnerships (IPI 2.4) surpassed the target of 75% and achieved an average score of 84%. The results also exceeded the 75% target for each criteria: Vision (89%), Leadership (80%), Accountability (80%), Communications (86%) & Collaboration and Impact (83%). Through extensive trainings and capacity development initiatives, IPI 3.3 - which looked precisely at how many respondents have used the products - scored an average of 77% for use, citing 439 unique examples of use. Continuous feedback on the survey design and results are also being compiled and will help improve the process for next year.